Integrated single-cell and bulk RNA sequencing analysis reveals ACACA as a potential prognostic and immunotherapeutic biomarker across cancers - He, Haihua; Zhang, Zhen; Chen, Leifeng; Gao, Fushan; Wu, Yuze; Yi, Lina; Shao, Fei; Gao, Yibo; He, Jie (Frontiers in Immunology, 2025)
BackgroundAcetyl-CoA carboxylase alpha (ACACA), a crucial rate-limiting enzyme governing de novo biosynthesis of fatty acids, drives oncogenic metabolic reprogramming in diverse malignancies. However, the multiomics investigation and immunological implications of ACACA across cancers remain unclear.MethodsWe performed a comprehensive pan-cancer analysis of ACACA via transcriptomic, proteomic, and clinical data from The Cancer Genome Atlas (TCGA), Clinical Proteomic Tumor Analysis Consortium (CPTAC), and the Human Protein Atlas (HPA) databases. Then, single-cell RNA sequencing acquired from the Gene Expression Omnibus (GEO) database was employed to map the expression pattern of ACACA in the tumor microenvironment (TME). Subsequently, functional validation experiments were conducted in lung cancer and sarcoma cells.ResultsHigh ACACA expression was associated with poor survival in various cancers, particularly those exhibiting dysregulated lipid metabolism. Immune profiling revealed that elevated ACACA expression was associated with low infiltration of CD8+ T cells and activated natural killer (NK) cells. Single-cell analysis of lung adenocarcinoma revealed that ACACA was expressed predominantly within malignant cells and contributed to an immunosuppressive microenvironment through migration inhibitory factor (MIF) signaling and the extracellular matrix (ECM) remodeling pathway. Furthermore, in vitro studies demonstrated that ACACA inhibition suppresses fatty acid synthesis and tumor growth in lung cancer and sarcoma cells.ConclusionsOur study establishes ACACA as a key metabolic regulator that links lipid metabolism to immune evasion and drug resistance, highlighting its potential as a promising therapeutic target across cancers.